PENGARUH HARGA TERHADAP PENINGKATAN PENJUALAN PRODUK SEMEN TIGA RODA PADA PT. ROBCAGA BEO KABUPATEN KEPULAUAN TALAUD - Gaghana, Cicilia Nitami; Tampi, J. R. E.; Kalangi, J. A. F. (Sam Ratulangi University, 2017)
The development in business world these days is market by the competition between the business company is getting fierce. Especially in managing the company business unit. It is shown by the appearance of a company that offer a good quality product with a compete price on the market. To handle the fierce competition on the market then one from so many effort that the company do is by apply the strategic price. Which on the way of applying that strategi the company try to set a price that can be compete in the market so the increase sale of the product become maximum. With right price and controlled will result the domino effect to a company to build long term relationship with costumer so it can increase the sales volume. This research is a descriptive quantitative research by using the correlation approach and simple regression. To see relation between variable and to measure the impact to the variable itself. So the purpose of this research is to know how far the price effect and to the increase of PT. ROBCAGA in Talaud. According to the sesult of the research, can be shown as following: price has a correlation and significant determination effort to the increase sale of PT. ROBCAGA Talaud. According to the data analysis, coefficient value moment r = 0,685. That show there is a positive relation, and can be categorize as high and strong, also price coefficient determination to the increase sale is by 46,5% and 53,5% by the rest of it depends on the unknown factors that not been analyze in this research. Keywords: Increase, price, sale